Front Cover: Helicene Bis(pyrazol‐1‐yl)pyridine Ligands for Luminescent Transition‐Metal Complexes (Eur. J. Inorg. Chem. 45/2019). Issue 45 (20th November 2019) - Abhervé, Alexandre; Martin, Kévin; Hauser, Andreas; Avarvari, Narcis
Abstract : The Front Cover shows one of the helicene‐based ligands that was designed and coordinated to transition metal ions against a background of the green Northern Lights of the Norwegian Lofoten Islands landscape, which symbolize the green emission of our tricarbonyl diimine rhenium complex. The red crystals at the bottom of the picture represent the complexes formed with our ligands. More information can be found in the Full Paper by A. Abhervé, N. Avarvari et al. For more on the story behind the cover research, see the Cover Profile.